Evolução da ceratoplastia lamelar posterior no tratamento das endoteliopatias da córnea - Pereira, Nicolas Cesario [UNIFESP] (2019)
Objectives: This thesis was carried out to evaluate the evolution of posterior lamellar keratoplasty in the treatment of endotheliopathies. Methods: 1. Review of the literature on the evolution of EK. 2. Retrospective review of EK performed by HOS second year cornea fellows between 2007 and 2008, describing early complications and their treatment. 3. A retrospective multicenter study of the first case series of 18 experienced surgeons from 11 different countries to document the results and complications of the DMEK technique during the learning curve. 4. Retrospective study of the first cases performed with a simplified DMEK technique, the "Samba" technique, describing the surgical technique, its results and complications. 5. This prospective study included the first consecutive series of 53 DMEK surgeries performed by corneal fellows at HOS. Results: 1. The literature review on the evolution of EK found different surgical techniques to replace the diseased endothelium. Compared to PK, these techniques are safer and offer better and faster visual rehabilitation. 2. There were 34 EK performed by HOS corneal fellows between July 2007 and August 2008. Of these, 29 were performed using the DSEK technique and 5 with DSAEK technique. The most common complication was graft detachment in 8 eyes (23.5%). Primary failure was found in 7 eyes (20.6%). 3. A total of 431 eyes were analyzed from 401 patients with Fuchs endothelial dystrophy (68.2%) and bullous keratopathy (31.8%) submitted to DMEK by 18 surgeons at the beginning of the learning curve in 11 different countries. Of the 275 eyes with data available for analysis of visual acuity, 217 eyes (78.9%) achieved BCVA of at least 20/40 (0.5), 117 (42.5%) at least 20/25 (0.8) and 61 (22.2%) at least 20 / 20 (1.0). Mean reduction of endothelial cell density at 6 months was 47% (20%) (n = 133 [P = 0.02]). The main postoperative complication was graft detachment (34.6%). 4. Of the 26 operated eyes by DMEK with the "Samba" technique, only 2 (7.7%) presented partial graft detachment requiring rebubbling. There were no cases of primary graft failure, tissue loss, or pupillary block. All patients with good visual potential achieved BCVA of 20/30 or better at 6 months. 5. Of the 33 eyes without ocular comorbities and with complete visual acuity measurements, 97% achieved a BCVA of ≥ 20/40 in 6 months. The mean (SD) preoperative donor ECD was 2453 (361)cells/mm2 and at 6 months postoperative the in vivo mean ECD (SD) was found to be 1300 (587) cells/mm2, an average loss of 47%. Preparation of the DMEK graft by the cornea fellows was successful in all cases. There were 9 eyes (17%) that experienced partial graft detachment requiring rebubbling. A total of 3 eyes (5.7%) failed to clear the cornea, all of which were managed with a successful secondary endothelial keratoplasty (EK). Conclusions: 1. EK is a treatment in evolution that represents a major advance over KP in the treatment of corneal endotheliopathies. DSEK / DSAEK are the most commonly used surgical techniques of EK, providing good visual results. Although more challenging, DMEK exhibits better visual results and lower rejection rate than DSEK / DSAEK. New perspectives, including endothelial cell therapy, may replace keratoplasty techniques for the treatment of corneal endothelial diseases. 2. DSEK / DSAEK have some advantages over PK, but have a long learning curve with potential complications. Beginning surgeons in these techniques must undergo training and have their first surgeries guided by experienced surgeons. 3. The international multicenter study of DMEK showed that the standardization of the “no-touch” technique is feasible for most surgeons, providing rapid visual rehabilitation and few complications. 4.The simplified "Samba" technique of DMEK showed to be reproducible, with good success rate and low number of complications, such as graft detachment, primary failure or pupillary block. 5. Establishing DMEK in a fellowship program with the supervision of an experienced DMEK surgeon was successful both in the preparation of the graft and in the visual results obtained.